Evaluation of lncRNA SOX2OT gene expression in breast cancer patients and its association with prognosis of disease: a paired sample study - Mahshid Yousefi; Mehdi Karimi; Abolhasan Rezaei; Masoud Mortezazadeh; Sheyda Akhshabi; Alireza Yousefi Ladmakhi; Niyousha Shirsalimi; Ehsan Kamali Yazdi; Seyyed Taher Seyyed Mahmoudi; Mehdi Kashani; Abbas Mofidi (Egyptian Journal of Medical Human Genetics)
Abstract Background and aim Breast cancer is a complex disease with genetic and molecular alterations. Long non-coding RNAs (lncRNAs), particularly SOX2 overlapping transcript (SOX2OT), are key regulatory molecules in cancer biology. Understanding SOX2OT expression patterns could provide insights into its potential as a biomarker for diagnosis and a target for therapeutic intervention. This study aimed to evaluate SOX2OT gene expression in breast cancer patients and its association with the disease’s prognosis. Methods This study was conducted in Tehran, Iran, in 2020. A total of 40 breast tissue samples were collected from 20 breast cancer patients, including 20 samples from tumor tissues and 20 from adjacent non-tumor marginal areas of the same patients. RNA extraction, cDNA synthesis, and Real-Time PCR analysis were performed, and the results were evaluated using SPSS statistical software. Results The results from RT-PCR showed that SOX2OT gene expression in cancer tumor samples was significantly 3.8 times higher than in non-tumor (control) samples (Fold change = 3.8; p = 0.025). This elevation was notably higher in patients with advanced-stage (III & IV) breast cancer (p = 0.02). A significant correlation was observed between SOX2OT expression and a family history of breast cancer (p = 0.031). In contrast, non-significant associations were found with other factors such as tumor size, lymphatic and vascular invasion, tissue necrosis, or smoking history. Conclusion The SOX2OT gene expression is significantly elevated in breast cancer tumors, particularly in advanced stages, suggesting its potential involvement in disease progression. The significant correlation between SOX2OT expression and a family history of breast cancer highlights a possible genetic influence. However, the lack of association with other clinical factors such as tumor size, tissue invasions, or smoking history suggests that SOX2OT expression may be more specifically linked to genetic predisposition and disease advancement rather than these factors.